Peningkatan Market Share Bank Syariah Melalui Kinerja Keuangan; Antara Moderasi Efisiensi Dan Risk-Taking Behavior - Ubaidi, Abdillah (MALIA: Journal of Islamic Banking and Finance, 2020)
Conducting analysis of efficiency, risk-taking behavior and market share of Islamic Banking in Indonesia. Conducted to answer the question of the still low market share of sharia banking in the national banking industry. The presence of Sharia Banking on dual banking system is still minimal. The monthly data sample of 34 Shariah Bank in Indonesia (11 Sharia Commercial Banks, 13 Sharia Business Units) is used to test the research hypothesis for the period from 2014 to 2017 using the estimator Generalized Method of Moments. The results show that there is a significant relationship and / or influence between the efficiency, risk-taking behavior and market share of Sharia Banking in Indonesia. Effect of moderation Efficiency and Risk-Taker Behavior on Financial Performance of Sharia Banking. Research limitations/ implications - Firstly, this paper focuses only on the sharia banking industry in Indonesia that adopts pro-active models, and therefore, expanding the investigation to include countries adopting different models may provide a better and more comprehensive view of the correlation between efficiency, risk-taking behavior and market share of Sharia Banking. Secondly, there is a need for more empirical data to be used, such as 7 years or more. This paper provides empirical evidence to regulators and policymakers in Indonesia, to understand how to increase the market share of sharia banking to the national banking industry. Furthermore, the sharia banking shareholder intends to increase the market share of sharia banking as one of the pillars of sharia finance in Indonesia which continues to grow. Previous studies have only discussed financial performance, efficiency and risk-taker behaviors without linking to market share levels. Because the discussion of market share is usually monopolized marketing studies..